The role of lncRNA CYTOR in human induced regulatory T cells - Pulliainen, Roosa (My University, 2024)
Regulatory T cells (Tregs) maintain tolerance against self-antigens and environmental allergens by suppressing excessive immune responses. Tregs are characterized by the expression of transcription factor Forkhead box p3 (Foxp3) which is known as the master regulator of Treg cells. However, Foxp3 alone is not sufficient to induce Treg phenotype and many other transcription factors also contribute to their development and function. Long non-coding RNAs (lncRNAs) have gained attention in recent years as potential important regulators in many biological processes. CYTOR (Cytoskeleton regulator) is an intergenic lncRNA which has been studied in several cancer types. However, very little is known about its expression in CD4+ T cells. CYTOR has an actively expressed paralog annotated as MIR4435-2HG. CYTOR shares 99.3 % homology with the 5’ end of MIR4435-2HG and differs from MIR4435-2HG by only 13 exonic single nucleotide exchanges. Due to this, CYTOR cannot be distinguished from the paralogous gene by knockdown approaches or quantitative PCR. However, most published CYTOR papers do not consider the paralogous gene. The aim of this study was to study the role of CYTOR/MIR4435-2HG during early differentiation of human induced regulatory T cells (iTregs) using gene knockdown approaches. The effects of CYTOR/MIR4435-2HG silencing on iTregs were assessed by studying Foxp3 expression on RNA and protein level, characterizing the expression of Treg-associated markers by flow cytometry and measuring the suppressive capacity of CYTOR/MIR4435-2HG-deficient iTregs by in vitro suppression assay. CYTOR/MIR4435-2HG silencing significantly reduced the expression of Foxp3 and other Treg-associated markers (e.g., CD25, CTLA-4 and PD-1) during early iTreg differentiation. Moreover, CYTOR/MIR4435-2HG-deficient iTregs were also less suppressive compared to control. This study suggests that CYTOR/MIR4435-2HG positively regulates early human iTreg differentiation and might play an important regulatory role in health and disease.
Keywords: Regulatory T cell, long non-coding RNAs, suppressive capacity